ENHANCEMENT OF POWER FACTOR CORRECTION IN AN AC-DC CONVERTER WITH AN INTEGRATED BOOST-FLYBACK CIRCUIT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Due to advancements in semiconductor technology, modern controllers, and nonlinear characteristics, loads are increasingly used in industrial applications. Because of nonlinear traits, harmonics are introduced in the main supply, and the supply current is distorted. Numerous power factor correction (PFC) converter topologies are established for proper wave shaping. The integration of conventional PFC converters produces superior results in high voltage on the output side and improves efficiency. A single-stage boost flyback integrated PFC converter is investigated in this paper, which provides high efficiency, high output voltage, and less voltage stress. This converter uses a lesser number of components, which results in a compact size and low cost. The enhancement of power factor, efficiency, and wave shaping of the current waveform is realized through various control techniques. A novel current sensorless control for the integrated topology is investigated, and it is shown that it provides better total harmonic distortion and current wave shaping than other control techniques. A 48 W, 12/48 V prototype model is implemented to validate the simulation results practically.
Keywords: Converter; Control techniques; Power factor correction; Wave shaping; Harmonics